2009
DOI: 10.1007/s10295-009-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic degradation of pyridine by a new bacterial strain, Shinella zoogloeoides BC026

Abstract: A new bacterial strain, Shinella zoogloeoides BC026, which utilizes pyridine as its sole carbon, nitrogen and energy source, was isolated from the activated sludge of a coking wastewater treatment plant. The BC026 strain completely degraded up to 1,806 mg/l of pyridine in 45.5 h. The optimum degradation conditions were pH 8.0 and temperature 30-35 degrees C. According to product monitoring and genetic analysis, the pyridine ring was cleaved between C(2) and N, resulting in 58% of pyridine-N being directly conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…20 days later, NH 4 + -N released was as high as approximately 130 mg L À1 , which was a bit higher than the stoichiometric amount, probably due to the digestion of the seed sludge inoculated in the ABR. As was reported by other researchers, nitrogen in the pyridine ring was often transformed into NH 4 + during pyridine biodegradation [10,43,44]. Therefore, the release of NH 4 + was a key evidence for pyridine ring cleavage.…”
Section: Start-up Of the Abr-mbbr Systemmentioning
confidence: 73%
See 1 more Smart Citation
“…20 days later, NH 4 + -N released was as high as approximately 130 mg L À1 , which was a bit higher than the stoichiometric amount, probably due to the digestion of the seed sludge inoculated in the ABR. As was reported by other researchers, nitrogen in the pyridine ring was often transformed into NH 4 + during pyridine biodegradation [10,43,44]. Therefore, the release of NH 4 + was a key evidence for pyridine ring cleavage.…”
Section: Start-up Of the Abr-mbbr Systemmentioning
confidence: 73%
“…Most of these studies were concentrated on the isolation and characterization of pyridine-degrading microorganisms [10,11], bioaugmentation of the bioreactors by adding pyridine-degrading microorganisms [11][12][13], immobilization of the microorganisms capable of degrading pyridine [14,15], and so on. However, considering the nauseating odour at aerobic condition, pyridine degradation under anaerobic or anoxic condition has attracted increasing interest in recent years [16].…”
Section: Introductionmentioning
confidence: 99%
“…6), the nirS and nosZ genes were found in six strains (BC039, BC040, BC041, BC044, BC045, and BC046) except BC043. The lengths of these gene fragments of the six strains were identical to other denitrifying bacteria [15,16,27]. We concluded that the six strains could convert NO 3 − and NO 2 − to N 2 .…”
Section: Pcr Amplification Of Functional Genes For Denitrificationmentioning
confidence: 89%
“…However, this type of system is difficult to operate due to the low rate of nitrification and the complexity of separating nitrification and denitrification reactors. Recently, bacteria capable of combined heterotrophic nitrification and aerobic denitrification has been investigated as potential microorganisms in biological nitrogen removal systems [2,4,9]. These microorganisms, due to their high growth rate and ability to convert ammonium (NH 4 ? ) to N 2 aerobically, have many advantages as applied for the removal of nitrogen: (1) procedural simplicity, where nitrification and denitrification can take place simultaneously; (2) less acclimation problems; (3) lesser buffer quantity needed because alkalinity generated during denitrification can partly compensate for the alkalinity consumption in nitrification [3].…”
Section: Introductionmentioning
confidence: 99%